2019
DOI: 10.1002/adma.201805944
|View full text |Cite
|
Sign up to set email alerts
|

Novel Molecular Doping Mechanism for n‐Doping of SnO2 via Triphenylphosphine Oxide and Its Effect on Perovskite Solar Cells

Abstract: Molecular doping of inorganic semiconductors is a rising topic in the field of organic/inorganic hybrid electronics. However, it is difficult to find dopant molecules which simultaneously exhibit strong reducibility and stability in ambient atmosphere, which are needed for n‐type doping of oxide semiconductors. Herein, successful n‐type doping of SnO2 is demonstrated by a simple, air‐robust, and cost‐effective triphenylphosphine oxide molecule. Strikingly, it is discovered that electrons are transferred from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
130
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(145 citation statements)
references
References 52 publications
7
130
0
Order By: Relevance
“…[92] ToF-SIMS also demonstrated the successful adoption of an electron donor triphenylphosphine oxide in SnO 2 , which realizes n-type doping of SnO 2 and enhances the conductivity of SnO 2 , enabling the increase of PCE from 19.01% to 20.69%. [93]…”
Section: Etlmentioning
confidence: 99%
“…[92] ToF-SIMS also demonstrated the successful adoption of an electron donor triphenylphosphine oxide in SnO 2 , which realizes n-type doping of SnO 2 and enhances the conductivity of SnO 2 , enabling the increase of PCE from 19.01% to 20.69%. [93]…”
Section: Etlmentioning
confidence: 99%
“…This strategy has been proved to be effective when applying on optoelectronics and energy devices. [82,83] Tu et al [84] successfully demonstrated an n-type doping of SnO 2 with an air-robust and cheap electron donor triphenylphosphine oxide (TPPO). It has three benzene rings at the three vertices in a plane and an oxygen atom at the other vertex.…”
Section: Organic Molecules-sno 2 Complexesmentioning
confidence: 99%
“…In a recent study from our group, [95] we introduced an inorganic compound, NH 4 Cl, into SnO 2 colloid dispersion and Reproduced with permission. [84] Copyright 2019, John Wiley and Sons. c) Energy band of PSCs, d) Current density versus voltage, and e) J-V curves of PSCs with different ETL.…”
Section: Introducing Inorganic Materialsmentioning
confidence: 99%
“…The most popular inorganic ETLs are transition metal oxides such as TiO 2 , 60 ZnO, 46 and SnO 2 . 61 Although the PSC devices using a TiO 2 ETL have achieved a relatively high efficiency (e.g., above 20%), this metal oxide exhibits some drawbacks such as low electronic conductivity and charge transport. 62,63 Hence, ZnO and SnO 2 , well known for their higher electron mobility (bulk mobility: 205-300 cm 2 V À1 s À1 64 and 240 cm 2 V À1 s À1 , 63 respectively) than that of TiO 2 (bulk mobility: 1 cm 2 V À1 s À1 63 ), have emerged as promising ETLs.…”
Section: Functions and Requirements Of Electron Transport Layersmentioning
confidence: 99%